Validation of SAGE III/ISS Solar Occultation Ozone Products With Correlative Satellite and Ground‐Based Measurements. Issue 11 (7th June 2020) - Wang, H. J. Ray; Damadeo, Robert; Flittner, David; Kramarova, Natalya; Taha, Ghassan; Davis, Sean; Thompson, Anne M.; Strahan, Susan; Wang, Yuhang; Froidevaux, Lucien; Degenstein, Doug; Bourassa, Adam; et al.
Abstract: The Stratospheric Aerosol and Gas Experiment III on the International Space Station (SAGE III/ISS) was launched on 19 February 2017 and began routine operation in June 2017. The first 2 years of SAGE III/ISS (v5.1) solar occultation ozone data were evaluated by using correlative satellite and ground‐based measurements. Among the three (MES, AO3, and MLR) SAGE III/ISS retrieved solar ozone products, AO3 ozone shows the smallest bias and best precision, with mean biases less than 5% for altitudes 15–55 km in the midlatitudes and 20–55 km in the tropics. In the lower stratosphere and upper troposphere, AO3 ozone shows high biases that increase with decreasing altitudes and reach 10% near the tropopause. Preliminary studies indicate that those high biases primarily result from the contributions of the oxygen dimer (O4 ) not being appropriately removed within the ozone channel. The precision of AO3 ozone is estimated to be 3% for altitudes between 20 and 40 km. It degrades to 10–15% in the lower mesosphere ( 55 km) and 20–30% near the tropopause. There could be an altitude registration error of 100 m in the SAGE III/ISS auxiliary temperature and pressure profiles. This, however, does not affect retrieved ozone profiles in native number density on geometric altitude coordinates. In the upper stratosphere and lower mesosphere ( 40–55 km), the SAGE III/ISS (and SAGE II) retrieved ozone values show sunrise/sunset differences of 5–8%, which are almost twice as large as what was observed by other satellites or model predictions. This feature needs further study. Key Points: Among the three SAGE III/ISS solar occultation retrievals, AO3 (v5.1) ozone product shows the smallest bias and the best precision The mean biases of AO3 ozone are less than 5% for 15–55 km in the midlatitudes and 20–55 km in the tropics. It increases to 10% near the tropopause The precision of AO3 ozone is 3% for altitudes 20–40 km. It degrades to 10–15% in the lower mesosphere ( 55 km) and 20–30% near the tropopause